2021
DOI: 10.1088/1757-899x/1052/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Method for Estimating Price of Second hand Ship with Multi Method

Abstract: Demand fleet as a means of marine transport could be met by building new ships and buying second-hand vessels. The current constraints in building a new ship are the cost relatively expensive and take a long time, while the profit for the procurement of second hand ships time relative faster and cheaper price. This study aimed to identify the price of second hand vessels and to develop a cost estimation model second hand vessels. Collecting data with survey vessel prices do with field surveys and market survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Floriano [5] established a model of the relationship between shipbuilder countries and second-hand ship prices and concluded that ships built in Japan and Europe often receive higher prices than other countries. Azhar A [6] builded a cost estimation model of a used ship to determine the price of a used ship andbuilds a cost estimation model of a used ship. The data was processed and analyzed by multiple methods including market price method, comparative ship and physical pricing method, and the estimated price or appraised ship is obtained from the average of the three methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Floriano [5] established a model of the relationship between shipbuilder countries and second-hand ship prices and concluded that ships built in Japan and Europe often receive higher prices than other countries. Azhar A [6] builded a cost estimation model of a used ship to determine the price of a used ship andbuilds a cost estimation model of a used ship. The data was processed and analyzed by multiple methods including market price method, comparative ship and physical pricing method, and the estimated price or appraised ship is obtained from the average of the three methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The estimated price of secondhand vessels can also be determined in the form of percentage reductions based on the life of the vessel [2] (table 1). Other more comprehensive methods are market price, comparative vessel and physical ship price, and the estimated ship price is obtained from the average value of the three methods [4], Figure 1. Fleet support in order to implement the sea toll program [1] The cost component of building a new ship from the results of another study consists of tangible and non-tangible factors [5].…”
Section: Introductionmentioning
confidence: 99%